Healing Beats 프로그램이 항암화학요법을 받는 대장암 환자의 스트레스, 심박동수 및 수면의 질에 미치는 효과: 무작위 대조군 실험연구 - 홍은정(Hong, Eun-Jeong) (Asian oncology nursing, 2024)
Purpose: This study aims to determine the effects of the Healing Beats program on stress, heart rate, and sleep quality in colorectal cancer patients treated with chemotherapy. Methods: The design of this study is a randomized controlled trial design. The data was collected from May 1, 2019 to August 31, 2019. The data of a total of 66 patients were collected and analyzed with 22 subjects in the experimental group, 22 in the placebo group, and 22 in the control group. The experimental group was to listen to the Healing Beats program of beats per minute equal to the subject's resting heart rate, and the placebo group was to listen to their favorite music. The control group did not participate in any sound listening treatment. Listening to music was performed four times a day, 20 minutes each time during the course of two days. stress, heart rate, subjective sleep quality, and number of awakenings were measured. Collected data were analyzed using SPSS Statistics 25.0. Results: The results of this study showed that the Healing Beats program had a positive effect on stress, subjective sleep quality, and number of awakenings in colorectal cancer patients treated with chemotherapy, and the difference was statistically significant (p<.05). Conclusion: The results of this study showed that the Healing Beats program that corresponded with the heart rate of subjects seems to be effective in reducing stress and improving sleep quality, and is expected to be used as stress and sleep management intervention. KCI Citation Count: 0